YIELD POTENTIAL OF DIRECT SEEDED RICE (ORYZA SATIVA L.) AS INFLUENCED BY DIFFERENT SEEDING TECHNIQUE AND WEED MANAGEMENT PRACTICES - KUMAR, KAUSHAL; U. N. SHUKLA; SINGH, MAHENDRA; SINGH, SMITA; SINGH, RAGHUVIR; PANT, ANIL KUMAR (The Bioscan, 2014)
A field experiment was conducted during kharif season 2007-08 at Crop Research Center of SVPUAT, Meerut and Uttar Pradesh to find out the suitable crop establishment method and weed management practices in rice. Effective tiller, (297.98), grain/panicle (143.84), grain yield (3711 kg/ha), straw yield (5808 kg/ha) and harvest index (38.98 %) produced higher under broadcast in puddled condition. Among weed management practices, higher number of productive tillers/m2, panicle length (28.79 cm), grains/panicle (148.3), test weight (22.48 g) and grain yield under butachlor @1.5 kg a.i. as pre-emergence followed by almix @ 4 g a.i./ha as post-emergence. Straw yield (5989 kg/ha) was significantly higher under butachlor @1.5 kg a.i. as pre-emergence followed by one hand weeding at 20-25 DAS (days after sowing).